Confiabilidad y validez de las listas de cotejos del exámen clínico objetivo estructurado para el aprendizaje por competencias de cirugía - Chávez Gil, Mario Alberty (2015)
Objective: To determine the validity and reliability of the check lists structured clinical examination (OSCE) for the 6th Year students of the Faculty of Medicine of the “Universidad Nacional de Trujillo” in 2011, in evaluating clinical performance of surgical skills of students. Methods: The research was carried out using check lists comparisons of the ten stations of the OSCE in different rotations. The stations used in general surgery patient simulator. In neurosurgery station used a plate computed tomography (CT) and the second used the Glasgow coma scale. In urology station used a patient simulator for renal colic and the second a model for Foley catheter placement. In ophthalmology, a station used a red-eye image and the second patient simulator study of fundus; Otolaryngology, a station used a CT simulator and the second patient assessment hearing test with fork. Results: We found that: the performance of surgical skills of 86 students was satisfactory (average qualification: 16 points); lists the 10 comparisons ECOE tests, in six stations reliability, using the split-half and correction Spearman-Brown, reached levels from 0.33 to 0.90 and four had reliability; as to the validity using Pearson correlation coefficient, Four Seasons had lists of valid comparisons and lists six stations were inaccurate comparisons. For statistical analysis SPSS version 15.0 was used. Conclusions: OSCE list of collations have satisfactory reliability and validity inaccurate. The performance was very satisfactory and the average was 16 points qualifier. Recommendations: Consider the results to reevaluate OSCE stations